The Impact of Sports Participation on the Psychological Well-Being of Employees of the Ministry of Youth and Sports of Iraq - Adeh Hamid, Rogayee; Badriazarin, Yaghoub; Javani, Vajiheh (Mental Health and Lifestyle Journal, 2025)
The objective of this study was to examine the effect of sports participation on the psychological well-being of employees of the Ministry of Youth and Sports of Iraq. This study employed a descriptive–applied field research design. The statistical population consisted of all employees of the Ministry of Youth and Sports of Iraq, from which the sample size was estimated using Krejcie and Morgan’s table. A convenience sampling method was applied to recruit participants. Data were collected using Ryff’s Psychological Well-Being Questionnaire (1989), which measures six dimensions of well-being including autonomy, environmental mastery, personal growth, positive relations with others, purpose in life, and self-acceptance. Descriptive statistics, including mean, standard deviation, and frequency distribution, were used for preliminary analysis. Structural equation modeling (SEM) with SmartPLS was applied to test the research hypothesis and assess the significance of relationships among variables. Reliability and validity were confirmed through Cronbach’s alpha, composite reliability, and average variance extracted (AVE). The results revealed that sports participation had a strong and significant effect on psychological well-being among employees of the Ministry of Youth and Sports of Iraq. The path coefficient from sports participation to psychological well-being was 0.943, with a t-value of 22.399 (p < 0.001), confirming the hypothesis. Furthermore, factor loadings for all measurement items exceeded the threshold of 0.40, and the model demonstrated high reliability and convergent validity, with all Cronbach’s alpha and composite reliability values above 0.70. These results confirm that increased engagement in sports activities significantly predicts higher levels of psychological well-being across all measured dimensions. The findings indicate that sports participation plays a critical role in enhancing the psychological well-being of employees. Promoting active lifestyles within the workplace can foster self-acceptance, autonomy, social relationships, and overall mental health, thereby contributing to individual wellness and organizational performance.